Transmission Network Expansion Planning Considering HVAC/HVDC Lines and Technical Losses - Dominguez, Andres H.; Escobar Zuluaga, Antonio H.; Macedo, Leonardo H. [UNESP]; Romero, Ruben [UNESP]; IEEE (Ieee, 2016)
This paper presents a mixed-integer linear programming (MILP) model to solve the transmission network expansion planning problem considering HVAC/HVDC links and power system losses. The use of an MILP model guarantees convergence to optimality by using existing classical optimization methods. The model was implemented using the modeling language AWL and solved using the solver CPLEX. The proposal was tested with the southern Brazilian electrical system of 46 buses and 79 candidate lines. The losses of both AC and DC lines are modeled as piecewise linear functions of the line flows. The DC transmission system may use either current source converters or voltage source converters. Sensitivity analysis for the cost of energy and planning horizon time were performed. The results show that DC links have the potential to be included in power system planning problems.
Keywords: HVDC; mathematical modeling; mixed-integer linear programming; transmission expansion planning